Parameters of leukopoiesis and thrombocytopenia in early urosepsis as potential predictors of a lethal outcome in hospitalized patients - S. V. Fedosenko; Yu. O. Rodionova; A. I. Ivanova; M. B. Arzhanik; O. L. Semenova; S. V. Nesterovich; E. A. Starovoitova; A. P. Zima; D. A. Vinokurova; E. М. Kamaltynova; V. V. Kalyuzhin (Бюллетень сибирской медицины)
Aim. To perform a comparative analysis of leukopoiesis parameters and platelet count in peripheral blood with evaluation of their changes in the first 48 hours from urosepsis (US) verification in hospitalized patients depending on the outcome of the disease.Materials and methods. A retrospective comparative study included 40 patients with US divided into a group of deceased (n = 10) and a group of recovered (n = 30) individuals. Along with a full clinical and paraclinical examination, which is a routine practice in the urology clinic in case of suspected (confirmed) sepsis, we performed a differentiated assessment of leukopoiesis and platelet count in peripheral blood at baseline (at the moment of US verification) and 48 hours after US verification. The assessment included determination of the immature granulocyte count, investigation of neutrophil granularity intensity (NEUT-GI) and neutrophil reactivity intensity (NEUT-RI), and measurement of the mean platelet volume (MPV).Results. The baseline level of organ dysfunction graded by the SOFA (Sequential Organ Failure Assessment) score was significantly higher in deceased patients than in survivors (6 points vs. 3 points, respectively; p = 0.001). The group of the deceased was characterized by lower platelet and monocyte levels. The ROC analysis with the calculation of area under the curve (AUC) identified the following potential predictors of a lethal outcome in US: proportion of monocytes from the total leukocyte count at baseline ≤ 5.5% (AUC 0.732, p = 0.032), proportion of eosinophils from the total leukocyte count at baseline ≤ 0% (AUC 0.756, p = 0.011), absolute eosinophil count at baseline ≤ 0.01 × 109 / l (AUC 0.802, p = 0.009), absolute basophil count at baseline ≤ 0.03 × 109 / l (AUC 0.718, p = 0.028), NEUT-GI at baseline ≤ 153.2 scatter intensity (SI) units (AUC 0.754, p = 0.021), NEUT-RI at baseline ≤ 59.3 SI units (AUC 0.737, p = 0.024) and their increase after 48 hours by > 0.9 SI units (AUC 0.852, p = 0.001) or by > 1.34% (AUC 0.844, p = 0.003), platelet count at baseline ≤ 144 × 109 / l (AUC 0.762, p = 0.007) and after 48 hours ≤ 174 × 109 / l (AUC 0.769, p < 0.007).Conclusion. The assessment of the platelet count and leukopoiesis parameters, including the ones characterizing neutrophil maturation (NEUT-RI, NEUT-GI), in the first 48 hours from US verification, can be effective predictors of a lethal outcome in patients with US.